(untitled) (Zoo Botanica, 2025)
This study genetic insights of spike-related inheritance traits in wheat (Triticum aestivum L.) under water stress. Seven wheat genotypes, comprising five drought-tolerant and two drought-sensitive lines, were crossed in all possible combinations in complete diallel fashion. The F1 hybrids and parental lines were tested under both irrigated and drought conditions in a randomized complete block design. Traits such as spikes plant-1, spike length, spikelets spike-1, spike weight, grains spike-1, spike harvest index, and grain yield plant-1 were recorded and analyzed. Significant genotypic variation was observed across all traits, with additive gene and partial dominance identified as the primary genetic mechanisms. Heritability estimates were moderate to high (40%–78%), highlighting the potential for genetic improvement. Traits like spikes per plant and spike length displayed high heritability under drought conditions, making them suitable targets for early-generation selection. The findings suggest that breeding programs focusing on additive gene action can enhance drought tolerance and yield potential in wheat. This research provides a framework for developing high-yielding, resilient wheat varieties suited for water-limited environments, through Identification of drought resilient crosses on the basis of studied traits contributing to sustainable food production also.